Physiological and molecular responses of black cumin (Nigella sativa L.) seedlings to silver nanoparticles. (26th November 2021) - Baniebrahim, Sara; Pishkar, Leila; Iranbakhsh, Alireza; Talei, Daryush; Barzin, Giti
Abstract: Due to their anti-bacterial and anti-fungal properties, silver (Ag) nanoparticles (AgNPs) are increasingly being used in consumer products. In this study, the effects of applying different concentrations of AgNPs (0, 2.5, 5, 10, 20, 40 and 80 mg L −1 ) on the growth, leaf concentrations of Ag, micro and macro-elements, leaf concentrations of malondialdehyde (MDA) and H2 O2, total antioxidant activity and activity of antioxidant enzymes in leaf extracts and leaf expression of phenylalanine ammonia-lyase ( PAL ) and chalcone synthase ( GSH ) genes were investigated in black cumin ( Nigella sativa ) seedlings. Results showed that AgNPs treatments led to increases in Ag concentrations in leaves and roots, with the accumulation in roots being slightly higher than leaves. AgNPs treatments at concentrations over 20 mg L −1 reduced growth, biomass production and accumulation of macro- (P, Mg and Ca) and micro-elements (Zn, Cu, Mn and B) and increased total antioxidant activity and MDA and H2 O2 contents. Application of AgNPs also increased the activity of the antioxidant enzymes superoxide dismutase (SOD), ascorbate peroxidase (APX), peroxidase (POD) and catalase (CAT) in leaf extracts when compared to the controls. The activity and expression of PAL and CHS enzymes also increased significantly with AgNPs treatment. Results indicate that the oxidative stress induced by AgNPs in black cumin plants is counteracted by increases in the activity of antioxidant systems and the expression and activity of PAL and CHS enzymes.